1990
DOI: 10.1080/00140139008927106
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an abdominal belt on trunk muscle activity and intra-abdominal pressure during squat lifts

Abstract: The purpose of this study was to determine whether abdominal belts such as those prescribed to industrial workers reduced trunk muscle activity and/or increased intra-abdominal pressure (IAP). In this study, six subjects lifted loads (72.7 to 90.9 kg) both with and without wearing a weightlifter belt. In addition, further trial conditions required that subjects lifted both with the breath held or continuously expiring on lifting effort. Dynamic hand loads were recorded together with intra-abdominal pressure (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
7

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(64 citation statements)
references
References 17 publications
5
52
0
7
Order By: Relevance
“…The magnitude of 9 kPa considered in this study for IAP in flexion tasks with load in hands is at the middle range of mean values reported in the literature (1-21 kPa) [2,31,36,44,52,53,55].…”
Section: Iap and Abdominal Coactivity Valuesmentioning
confidence: 61%
See 4 more Smart Citations
“…The magnitude of 9 kPa considered in this study for IAP in flexion tasks with load in hands is at the middle range of mean values reported in the literature (1-21 kPa) [2,31,36,44,52,53,55].…”
Section: Iap and Abdominal Coactivity Valuesmentioning
confidence: 61%
“…Experimental studies, however, have found that IAP increase is associated with a concurrent increase in the intradiscal pressure during Valsalva maneuvers [55] and no reduction in erector spinae activity in lifting [42,52]; thus raising questions on the unloading role of IAP. The co-contraction of abdominal muscles occurring along with an increase in IAP produces a flexor moment, large enough to offset or even exceed the IAP-generated extensor moment [11, 49,52].…”
Section: N Arjmand a Shirazi-adlmentioning
confidence: 99%
See 3 more Smart Citations